Geobacter sp. SD‐1 with enhanced electrochemical activity in high‐salt concentration solutions. Issue 6 (16th July 2014) - Sun, Dan; Call, Douglas; Wang, Aijie; Cheng, Shaoan; Logan, Bruce E.
Summary An isolate, designated strain SD‐1, was obtained from a biofilm dominated by Geobacter sulfurreducens in a microbial fuel cell. The electrochemical activity of strain SD‐1 was compared with type strains, G. sulfurreducens PCA and Geobacter metallireducens GS‐15, and a mixed culture in microbial electrolysis cells. SD‐1 produced a maximum current density of 290 ± 29 A m−3 in a high‐concentration phosphate buffer solution (PBS‐H, 200 mM). This current density was significantly higher than that produced by the mixed culture (189 ± 44 A m−3) or the type strains (< 70 A m−3). In a highly saline water (SW; 50 mM PBS and 650 mM NaCl), current by SD‐1 (158 ± 4 A m−3) was reduced by 28% compared with 50 mM PBS (220 ± 4 A m−3), but it was still higher than that of the mixed culture (147 ± 19 A m−3), and strains PCA and GS‐15 did not produce any current. Electrochemical tests showed that the improved performance of SD‐1 was due to its lower charge transfer resistance and more negative potentials produced at higher current densities. These results show that the electrochemical activity of SD‐1 was significantly different than other Geobacter strains and mixed cultures in terms of its salt tolerance.